HYBRIDIZATION OF MINGLING MAGMAS WITH DIFFERENT DENSITIES - Albarede F.; Grasset O. (My University, 1995)
It is usually assumed that chemical exchange between mafic enclaves considered as blobs of mafic liquids and their host silicic melt proceeds through static diffusion. However, the chemical boundary layer should keep the interior of magmatic enclaves nearly pristine, a feature which is not observed. The surface layer of a mafic blob falling in a more silicic melt is likely to be continuously folded in with the inner part. A numerical model shows that buoyancy-driven forced convection is an efficient way of enhancing the rate at which melt inclusions become hydrous and hybridized by the host melt.